Salt Therapy for Health as an Alternative Additional Activities on The Tunnel Model in The Buffer Group Pliwetan Village Palang District Tuban Regency - Suwarsih Suwarsih; Marita Ika Joesidawati; Perdana Ixbal Spanton; Raka Nur Sukma (Kontribusia : Research Dissemination for Community Development, 2022)
Pliwetan Village, Palang District, Tuban Regency is an area with the potential to produce salt and the highest production compared to the surrounding environment. This is because, in this area, there are salt ponds that use the tunnel method owned by partners or groups of buffer salt farmers—the use of tunnel salt land as a tool for health therapy. This Community Service activity was carried out in the buffer salt farmer group of Pliwetan Village, Palang District, Tuban Regency with a duration of time being carried out in March 2022. The parties involved in this activity are: Fisheries and Marine Science lecturers, PGRI Ronggolawe University and partner groups of the Buffer Salt Farmers Group who play an active role as participants in every activity carried out in community service activities. The realization of the results of this activity is to provide counseling and assistance on how to use the salt tunnel land for health therapy, review of the results of achievements in the form of assistance in the practice of salt therapies for health so that it is hoped that the public understands the benefits of salt therapy for people health